1990
DOI: 10.1080/02724936.1990.11747453
|View full text |Cite
|
Sign up to set email alerts
|

An epidemic of dengue haemorrhagic fever and dengue shock syndrome in Delhi: a clinical study

Abstract: Twenty-four cases of dengue haemorrhagic fever/dengue shock syndrome were studied in Delhi in the months of September and October, 1988. The majority of these cases were boys aged 6-10 years. Classical symptoms of dengue (fever, headache, aesthesia, myalgia) occurred in all the patients. Digestive symptoms (nausea, vomiting, anorexia, abdominal pain and hepatomegaly) were also common. Haemorrhagic manifestations were present in 41.7% of the cases. Of these, 90% had gastrointestinal haemorrhages. Shock occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
1
2

Year Published

2002
2002
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 5 publications
7
23
1
2
Order By: Relevance
“…14,15 Various other factors apart from thrombocytopenia lead to bleeding manifestations, which are decreased platelet function, fibrinogen consumption, prolongation of PT/PTT, and vasculopathy. 16 Hepatomegaly was observed in majority of cases of severe dengue in our study, as reported in studies of Joshi R, Srivastava VK et al 17,18 55% of cases in our study had raised haematocrit, with only 7 cases of severe dengue fever. But findings of Agarwal et al reported much lower incidence of cases with raised haematocrit which does not coincide with our findings.…”
Section: Discussionsupporting
confidence: 72%
“…14,15 Various other factors apart from thrombocytopenia lead to bleeding manifestations, which are decreased platelet function, fibrinogen consumption, prolongation of PT/PTT, and vasculopathy. 16 Hepatomegaly was observed in majority of cases of severe dengue in our study, as reported in studies of Joshi R, Srivastava VK et al 17,18 55% of cases in our study had raised haematocrit, with only 7 cases of severe dengue fever. But findings of Agarwal et al reported much lower incidence of cases with raised haematocrit which does not coincide with our findings.…”
Section: Discussionsupporting
confidence: 72%
“…However, no correlation was possible between prolonged PT, APTT and prognosis. Hypoalbuminemia was seen in 38.0% and comparable to previous sudy by Srivastava et al; higher percentage (76.0%) of hypoalbuminemia was reported by Aggarwal A et al 31,35 Mishra S et al report the prevalence of DHF to be 13.4% (n=13) in their paediatric patients, with greater affliction in >11 years (n=09). 36 There were more number of males (n=09) with severe dengue.…”
Section: 12-14supporting
confidence: 70%
“…In the study by Srinivas et al [26], fever and vomiting were the most frequent symptoms. Similar observation was also seen in earlier studies [14,28,29]. Srinivasa also observed rashes in 10.5% cases while Ahmed FU et al [30] noted rashes in 12% of children.…”
Section: Discussion:-supporting
confidence: 77%